2006
DOI: 10.1523/jneurosci.2339-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Decorrelation Sensitivity of Auditory Nerve and Anteroventral Cochlear Nucleus Fibers to Broadband and Narrowband Noise

Abstract: Binaural neurons show remarkable sensitivity to temporal differences in the waveforms at the two ears. This ability obviously requires temporal coding of sound waveforms in the monaural afferents that converge on such binaural neurons. We introduce a new analysis to investigate how well responses of single monaural neurons support discrimination of decorrelations in waveforms. Spike trains from auditory nerve (AN) and anteroventral cochlear nucleus (AVCN) neurons of cats to many repetitions of a set of broadba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 44 publications
5
43
0
Order By: Relevance
“…The neural cross-correlation metrics developed here represent an extension of shuffled auto-and crosscorrelogram analyses recently developed by Joris and colleagues (Joris 2003;Louage et al 2004Louage et al , 2006Joris et al 2006a, b). These neural metrics provide normalized representations of correlated temporal coding computed as the degree of common temporal fluctuations in two-spike trains (cross-correlograms) relative to the degree of temporal coding within each spike-train response individually (autocorrelograms).…”
Section: A Normalized Representation Of Neural Cross-correlationmentioning
confidence: 99%
“…The neural cross-correlation metrics developed here represent an extension of shuffled auto-and crosscorrelogram analyses recently developed by Joris and colleagues (Joris 2003;Louage et al 2004Louage et al , 2006Joris et al 2006a, b). These neural metrics provide normalized representations of correlated temporal coding computed as the degree of common temporal fluctuations in two-spike trains (cross-correlograms) relative to the degree of temporal coding within each spike-train response individually (autocorrelograms).…”
Section: A Normalized Representation Of Neural Cross-correlationmentioning
confidence: 99%
“…The stimulus is illustrated schematically in Fig. 1, I and J and a more detailed description can be found in Louage et al (2006). Two independent tokens of Gaussian broadband noise (lower cutoff 50 or 100 Hz; upper cutoff between 8 and 10 kHz) were either presented unmixed as reference tokens or combined to produce different mixed tokens.…”
Section: Ic Stimulimentioning
confidence: 99%
“…Interaural correlation values were either evenly spaced, as in the IC experiments, or spaced unequally to maximize the sampling close to an interaural correlation of 1 (1, 0.99, 0.96, 0.911, 0.844, 0.76, 0, Ϫ1) (Louage et al 2006).…”
Section: Construction Of "Binaural" Responses From An Datamentioning
confidence: 99%
“…However, in measurements of IAC sensitivity (Shackleton et al 2005), we found that the neural thresholds did not match the behavioral thresholds, being at least three times worse. Thus, although IAC and ITD discrimination are closely linked theoretically (e.g., Colburn and Durlach 1978;Durlach et al 1986;Koehnke et al 1986;Shackleton et al 2005;Louage et al 2006), they appear to be give different results.…”
Section: Introductionmentioning
confidence: 98%